Customer Loyalty Model of Export Product Shipment Certification - Muchdy Lubis; Hartoyo Hartoyo; Nimmi Zulbainarni (Widya Cipta: Jurnal Sekretari dan Manajemen, 2025)
This study explores a loyalty model for customers of PT. XYZ, a certification body managing export product shipment certification. It examines the role of service quality, customer satisfaction, trust, and loyalty and aims to identify areas for improvement. The questionnaires were distributed to 119 companies, but only 104 companies became research respondents. The data was collected using convenience sampling and telephone surveys. Results indicate that customer satisfaction is significantly shaped by five Servqual service quality dimensions: tangibility, empathy, reliability, responsiveness, and assurance. These dimensions also substantially influence customer trust. Satisfaction and trust directly affect customer loyalty, with indirect effects mediated through trust. Specifically, reliability impacts trust via satisfaction, and assurance impacts trust through satisfaction. Satisfaction, in turn, drives loyalty through trust. For further improvements in service quality, it is recommended PT. XYZ conducts training personnel in communication and regulatory compliance. PT. XYZ is also suggested to conduct document control and personal protective equipment management training.